Recent advances of nanofluids in micro/nano scale energy transportation. (October 2021) - Liu, Changhui; Qiao, Yu; Du, Peixing; Zhang, Jiahao; Zhao, Jiateng; Liu, Chenzhen; Huo, Yutao; Qi, Cong; Rao, Zhonghao; Yan, Yuying
Abstract: As the continuing integration and size deflation of component dimensions in electronic circuits and increase in the number of transistors in modern microprocessor chips, especially for heat dissipation of micro/nano scale devise, traditionally used single phase fluid cannot meet the requirements for highly efficient heat transfer, which thus frequently results in the damage of electrical devices. Consequently, thermal conductivity enhancement of working fluids is of great significance for advanced thermal energy conservation and conversion. Nanofluids, which possess a superior thermal conductive performance, are studied towards an alternative to the traditionally used working fluids, have attracted ample attention within the past decades. In this paper, firstly, we summarized the recent progress in the preparation of nanofluids, in particular for a method involving a covalent concerning reorganization or generation; subsequently, the utilization of nanofluids in hitherto unsummerized micro/nano scale heat and mass transfer fields, especially for some chemistry relating applications were discussed. All works demonstrated in this review are aiming at clarifying the fact that advanced material technologies are required in preparation of recent nanofluids on the premise of continuing harsh energy transfer situation; on the other hand, nanofluids were also able to offer insights for novel micro/nano scale energy transportation which has not yet been reviewed before. Highlights: Preparation of nanofluids in a covalent reorganization was summarized. Hitherto unsummerized micro/nano scale energy transportation of nanofluids was reviewed. Nanofluids provide new insights towards novel materials development.